Application of Nanotechnology for the Development of a Next Generation Dental Restorative Material - Radu Claudiu Fierascu; Anda Maria Baroi; Roxana Ioana Matei (Brazdis); Toma Fistos; Irina Fierascu; Ioana Silvia Hosu; Irina Elena Chican; Lia Mara Ditu (Proceedings)
The two most common oral diseases, caries and periodontal disease, are very abundant among the population of industrialized countries, having a major impact on the well-being of the population and medical service providers. Millions of people around the world suffer from toothache due to tooth decay and this often leads to permanent tooth loss. The aim of the current study is to present the development and characterization of a composite material containing a glass ionomer cement and phytosynthesized metallic nanoparticles, intended for dental applications.